Changing modes of public connection: an essay on TikTok and the social affordances of personalized social media - Schellewald, Andreas (Frontiers in Computer Science, 2025)
The short-video app TikTok has become one of the most used social media platforms globally. Its affordances are distinctly different from those of prior apps and platforms—specifically due to TikTok’s algorithm-centric design. This essay critically reflects on the consequences of this design logic, especially in relation to modes of public connection, resistance, and social change. Reflecting on ethnographic fieldwork on TikTok, it opens three perspectives: (1) on the modes of disconnected sociability that TikTok’s “For You” page affords, (2) the forms of infrapolitical resistance that materialize within the textual structure of the “For You” page, and (3) the importance of creativity as an element of the consumption process shaping its social meaningfulness. Across these three perspectives, the essay argues that TikTok affords relatively unique modes of public connection which, ultimately, can only be understood in their real consequences when viewed as integrated parts of the micro-social world where people’s day-to-day lives unfold.